2016
DOI: 10.1002/yea.3218
|View full text |Cite
|
Sign up to set email alerts
|

Naumovozyma castellii: an alternative model for budding yeast molecular biology

Abstract: Naumovozyma castellii (Saccharomyces castellii) is a member of the budding yeast family Saccharomycetaceae. It has been extensively used as a model organism for telomere biology research and has gained increasing interest as a budding yeast model for functional analyses owing to its amenability to genetic modifications. Owing to the suitable phylogenetic distance to S. cerevisiae, the whole genome sequence of N. castellii has provided unique data for comparative genomic studies, and it played a key role in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The budding yeast Naumovozyma castellii (also known as S. castellii ), which belongs to the family of Saccharomycetaceae, has been extensively used for studies in comparative genomics and molecular evolution. Its amenability for genetic modification has rendered it a feasible model organism for molecular genetic functional analyses and it has significantly contributed with discoveries of fundamental molecular mechanisms in the fields of centromeres, mitochondria, RNAi and telomeres 37 . The telomeres of N. castellii share many features with those of human cells.…”
Section: Introductionmentioning
confidence: 99%
“…The budding yeast Naumovozyma castellii (also known as S. castellii ), which belongs to the family of Saccharomycetaceae, has been extensively used for studies in comparative genomics and molecular evolution. Its amenability for genetic modification has rendered it a feasible model organism for molecular genetic functional analyses and it has significantly contributed with discoveries of fundamental molecular mechanisms in the fields of centromeres, mitochondria, RNAi and telomeres 37 . The telomeres of N. castellii share many features with those of human cells.…”
Section: Introductionmentioning
confidence: 99%
“…As positive controls for linear chromosomes, we analyzed karyotypes of the parental strain and two isogenic WT strains obtained from the same tetrad, which all showed eight chromosomal bands in the PFGE (Figure 5A, lanes 1 and 3-4). As N. castellii was previously shown to have 10 chromosomes in the whole genome sequencing approach, probably some of the chromosomes are not resolving on the PFGE gel (Cliften et al 2006; Gordon et al 2011; Karademir Andersson and Cohn 2017). This notion is supported by the variation in signal intensity of the bands, suggesting that some bands include overlapping chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The budding yeast Naumovozyma castellii has been used as a model organism in telomere studies owing to its human-like telomere structure and maintenance (Karademir Andersson and Cohn 2017). N. castellii belongs to an evolutionary lineage that underwent whole genome duplication followed by a massive gene loss (Cliften et al 2006; Karademir Andersson et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that in Naumovozyma, an unconventional centromere has come into existence at a location that is largely distinct from that expected based on synteny with other Saccharomycetaceae species (Kobayashi et al, 2015). The Naumovozyma genus has been suggested as a model for comparative genomics and study of adaptive evolution due to the various phenotypic differences compared to other yeast species (Karademir Andersson & Cohn, 2017).…”
Section: Introductionmentioning
confidence: 99%